ANALISIS USAHATANI KAKAO PADA DUA POLA TANAM POLIKULTUR (Forum Agribisnis, 2017)
The Contributions of cocoa plantations to the profit of farmers is an important issue for the farm development. Cocoa plant is annual plant that can produce throughout the year. In Order to increase profit and Reduce the risk of crop failure, farmers applying polyculture pattern. Application of intercropping patterns on their farm has a linkage with the structure of the costs incurred to cultivate these plants.The purpose of this study is to analyze the level of income and efficiency of the two cropping pattern with the combination of 2 (cocoa and clove) and 3 (cocoa, clove, and coffee) commodities.  The method of data collection conducted randomly collected as many as 49 farmers that working on 2 commodities using polyculture cropping pattern and 33 farmers that working on 3 commodities using polyculture cropping pattern.  The analytical results showed that the farmers that working on 3 commodities using polyculture cropping pattern have low production level, income, and efficiency, but this polyculture system is still running continuously by the farmers, because it is profitable and has a good efficiency.